2000
DOI: 10.1007/bf02704353
|View full text |Cite
|
Sign up to set email alerts
|

Charge-transfer spectra of ferrocene in halocarbon solvents under photoexcitation

Abstract: The changes in the electronic absorption spectra of ferrocene in the halocarbon solvents chloroform and carbontetrachloride have been investigated under photoexcitation in nitrogen atmosphere. Photoexcitations have been made with monochromatic light (using an Xe-source and a monochromator), at intervals of a few nanometers in the spectral range 220-750 nm. Analysing the spectra by a modified method the position of the charge-transfer-to-solvent (CTTS) band has been located for both the solvents. The position o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
3
4
0
Order By: Relevance
“…The shape of the UV–visible absorption spectrum of the new synthesized dyads in chloroform is different from that in other solvents. In polyhalogenated solvents such as chloroform, formation of charge transfer complexes of ferrocene with solvent occurs, this ferrocene to solvent charge transfer phenomenon having been predicted in previous studies …”
Section: Resultssupporting
confidence: 59%
“…The shape of the UV–visible absorption spectrum of the new synthesized dyads in chloroform is different from that in other solvents. In polyhalogenated solvents such as chloroform, formation of charge transfer complexes of ferrocene with solvent occurs, this ferrocene to solvent charge transfer phenomenon having been predicted in previous studies …”
Section: Resultssupporting
confidence: 59%
“…When these compounds were probed in the SDS negative membrane a new band at about 650 -715 nm was appeared, This new band may be assigned to the oxidation of ferrocene to ferrocenium specie in accordance with literature[37].…”
supporting
confidence: 85%
“…Ferrocene-based polymeric systems are some of the most well-studied organometallic macromolecules, and their electrochemical properties have also been studied extensively. 2c, It has been shown by Manners and co-workers that communication between iron centers in polymers is dependent on the nature of the organic/inorganic bridging groups 1e. Recently, it was shown that silicon-bridged [1]ferrocenophanes undergo photolytic living ring-opening polymerization in the presence of nucleophilic anionic initiators . It was proposed that the ring-opening of the [1]ferrocenophanes was facilitated via photoinduced MLCT transitions, which further weakened the already weak Fe−Cp bonds, thus allowing for nucleophilic attack at the iron centers 7a.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that silicon-bridged [1]ferrocenophanes undergo photolytic living ring-opening polymerization in the presence of nucleophilic anionic initiators . It was proposed that the ring-opening of the [1]ferrocenophanes was facilitated via photoinduced MLCT transitions, which further weakened the already weak Fe−Cp bonds, thus allowing for nucleophilic attack at the iron centers 7a. The resulting poly(ferrocenylsilanes) were not photoactive since the HOMO−LUMO transition for these polymers was similar to that of ferrocene and exhibit no significant MLCT character.…”
Section: Introductionmentioning
confidence: 99%